PENANGGULANGAN KEMISKINAN BERBASIS PARTISIPASI MASYARAKAT DI PROVINSI BALI - Murjana Yasa, I G. W. (INPUT Jurnal Ekonomi dan Sosial; Vol. 1, No. 2 Agustus 2008, 2012)
Main development problem in developing country is the contradiction between unemployment and poverty. It is caused by the strong relation between both problem. Poverty in so many cases mostly started by the lack access of productive human source to the job ? eld. The complexity of the problem drive the worldwide commitment in reducing poverty all over the world by the draft of development goals, called Millennium Development Goals (MDGs) To promote the development, the effort to reduce poverty that mainly started by the unemployment must involve the society in participative platform. The participation pattern possibly reducing poverty to be more grounded, strengthen commitment between society in responsibility to reduce unwelfare . The local genius, for instance Lembaga Perkreditan Desa (LPD) that is own by the village association has the strategic role in reducing poverty trough the improvement of its social function beside the main function which is to improve the members welfare. The social function means the commitment and togetherness between member to institution and between members.
Keywords: Poverty, development, MDGs